Utilization of Information and Communication Technologies (ICTs) for water management, marketing and weather forecasting - KUMAR, RUPENDER; HUDDA, R S; YADAV, KRISHAN; MANJEET, MANJEET (The Indian Journal of Agricultural Sciences, 2018)
The present study was carried out in randomly selected four districts of Haryana namely, Yamunanagar, Karnal, Hisar and Fatehabad. In total 240 respondents comprising 15 farmers from 16 villages were selected randomly in 2016-17. Majority of the farmers used ICTs to ascertain the water supply in channel before sowing time followed by advance information about time and date of supply of water in canal for complete crop period. Farmers used ICTs to know about place of marketing, marketing price, time of market inflow, quality parameters that eventually affect commodity price, marketing procedure and other facilities available at market. Majority of the farmers used ICTsfor the purpose of information, i.e. weather forecasting, crops related government policies, credit/loan facilities for crops cultivation, insurance and subsidies for crop cultivation.